The Potential of Films as Transmucosal Drug Delivery Systems - Ana Clara Wada de Carvalho; Natália Floriano Paiva; Isabella Kriunas Demonari; Maíra Peres Ferreira Duarte; Renê Oliveira do Couto; Osvaldo de Freitas; Fabiana Testa Moura de Carvalho Vicentini (MDPI AG, 2023)
Pharmaceutical films are polymeric formulations used as a delivery platform for administration of small and macromolecular drugs for local or systemic action. They can be produced by using synthetic, semi-synthetic, or natural polymers through solvent casting, electrospinning, hot-melt extrusion, and 3D printing methods, and depending on the components and the manufacturing methods used, the films allow the modulation of drug release. Moreover, they have advantages that have drawn interest in the development and evaluation of film application on the buccal, nasal, vaginal, and ocular mucosa. This review aims to provide an overview of and critically discuss the use of films as transmucosal drug delivery systems. For this, aspects such as the composition of these formulations, the theories of mucoadhesion, and the methods of production were deeply considered, and an analysis of the main transmucosal pathways for which there are examples of developed films was conducted. All of this allowed us to point out the most relevant characteristics and opportunities that deserve to be taken into account in the use of films as transmucosal drug delivery systems.